2003
DOI: 10.1518/hfes.45.1.160.27234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Head-Slaved Navigation and the Use of Teleports on Spatial Orientation in Virtual Environments

Abstract: The type of navigation interface in a virtual environment (VE)--head slaved or indirect--determines whether or not proprioceptive feedback stimuli are present during movement. In addition, teleports can be used, which do not provide continuous movement but, rather, discontinuously displace the viewpoint over large distances. A two-part experiment was performed. The first part investigated whether head-slaved navigation provides an advantage for spatial learning in a VE. The second part investigated the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…On the other hand, compared to continuous viewpoint transition, instant viewpoint transition (teleportation) was found to cause more spatial disorientation. Bakker et al (2003) Compared teleportation with and without anticipation. They found that anticipation to an extent helped avoiding disorientation resulting from teleportation.…”
Section: Studies With Teleportationmentioning
confidence: 99%
“…On the other hand, compared to continuous viewpoint transition, instant viewpoint transition (teleportation) was found to cause more spatial disorientation. Bakker et al (2003) Compared teleportation with and without anticipation. They found that anticipation to an extent helped avoiding disorientation resulting from teleportation.…”
Section: Studies With Teleportationmentioning
confidence: 99%
“…Virtual environments can be more complex than natural environments with respect to their scale [4,2], structural complexity and dimensionality [5]. Furthermore, virtual environments often differ from natural environments with respect to the sensory modalities involved, depending on the use of visual, auditory and vestibular displays [6,7,8,9,10,11] and interaction methods [8]. Thus, an optimal support of human spatial navigation in virtual environments relies on knowing the effects of involving multiple sensory modalities.…”
Section: Introductionmentioning
confidence: 99%
“…While some variants of teleportation limit the users to fixed teleportation destinations (i.e., fix-point teleportation), studies have shown that free teleportation leads to a lower discomfort [13]. Although teleportation can lead to disorientation [2,6], it was subjectively preferred over joystick input in a study by Langbehn et al in 2018 [17].…”
Section: Locomotion In Vrmentioning
confidence: 99%